The membrane may be a key factor influencing browning: a mini review on browning mechanisms of fresh-cut fruit and vegetables from a multi-omics perspective - Yuan, Xiao; Zhan, Zhaoxia; Lin, Wei; Zhang, Can; Wang, Bin (Frontiers in Nutrition, 2025)
Fresh-cut fruit and vegetables are susceptible to browning during storage and subsequent consumption. The cell membrane acts as a vital structural barrier, compartmentalizing various substances within living organisms. The fresh-cutting process induces mechanical injuries, disrupting these membranes and resulting in the leakage of cellular contents. This facilitates direct contact between substances and enzymes that mediate browning reactions. This mini review explores the potential roles of cell membranes in the browning of fresh-cut fruit and vegetables from a multi-omics perspective, aiming to provide novel insights into the underlying mechanisms of browning in fresh-cut fruit and vegetables. Considering potential roles of cell membranes in blocking the browning of fresh-cut fruit and vegetables, future studies should focus on elucidating the precise mechanisms by which membranes regulate browning reactions, aiming to provide directions for the development of more effective intervention strategies.